Inbreeding reduces fitness of seed beetles under thermal stress. (20th July 2021) - Ivimey‐Cook, Edward; Bricout, Sophie; Candela, Victoria; Maklakov, Alexei A.; Berg, Elena C.
Abstract: Human‐induced environmental change can influence populations both at the global level through climatic warming and at the local level through habitat fragmentation. As populations become more isolated, they can suffer from high levels of inbreeding, which contributes to a reduction in fitness, termed inbreeding depression. However, it is still unclear if this increase in homozygosity also results in a corresponding increase in sensitivity to stressful conditions, which could intensify the already detrimental effects of environmental warming. Here, in a fully factorial design, we assessed the life‐long impact of increased inbreeding load and elevated temperature on key life history traits in the seed beetle, Callosobruchus maculatus . We found that beetles raised at higher temperatures had far reduced fitness and survival than beetles from control temperatures. Importantly, these negative effects were exacerbated in inbred beetles as a result of increased inbreeding load, with further detrimental effects manifesting on individual eclosion probability and lifetime reproductive success. These results reveal the harmful impact that increasing temperature and likelihood of habitat fragmentation due to anthropogenetic changes in environmental conditions could have on populations of organisms worldwide. Abstract : Human‐induced environmental change can influence populations both at the global level through climatic warming and at the local level through habitat fragmentation and inbreeding. We found that seed beetles raised at higher temperatures had far reduced fitness than beetles from control temperatures and these negative effects were exacerbated when individuals were inbred.